Estudo do comportamento mecânico de córneas via simulações numéricas - Almeida, Paulo Roberto de (2016)
Cornea and sclera are parts of the ocular globe external surface, providing protection to the sensitive internal components and keeping the shape of eye refractive. The corneal structure is composed by epithelium, endotheliumn and stroma, being this last one the main responsible for the mechanical properties of the cornea. Corneal stiffness problems can affect people due age of the patient and the treatment requires the availability of specialized instruments. This may limit the treatment of patients who do not have access to specialized centers and availability of financial resources. The development of numerical models customized for each patient could eliminate the need of these treatments, since only numerical simulations could accomplish certain procedures, significantly reducing costs. Furthermore, the development of an effective alternative, with a reduced cost and without the need for specialized tools for treating patients with in cornea rigidity problems is exterma importance. This work proposes an analysis of the mechanical behavior of human corneas via numerical simulations, in terms of development of a finite element model to measure the displacement at the cornea central point from an internal pressure, in order to obtain mechanical characteristics, as example the cornea rigidity. Experimental data from mechanical behavior of human cornea were obtained in collaboration with the University of Liverpool, more precisely in Ocular Biomechanics Laboratory. Simulations were performed using Abaqus® software varying the amount of elements, nodes and patients age, aiming to confront with the experimental data. Results show that increasing the cornea stiffness is proportional to the increasing of the patient age and increasing the number of nodes in the finite element model of the cornea, the error decreases towards the experimental value.